Extra-stimulus influences on eyewitness perception and recall: hastorf and Cantril revisited - Boon, Julian (Legal and criminological psychology, 1996)
In a classic study by Hastorf & Cantril (1954), partisan relationships to the viewing of an American football game were shown to be related to personal judgments of culpability for on-field offences. While this finding has been widely cited as evidence for unwitting, inherent distortion in eyewitness testimony, the study's original purpose and methodology were not congruent to such a claim. A study is presented which draws on the basic paradigm of the earlier work but which attempts to update its methodology with a view to considering the potential implications for eyewitness concerns. This modernized study found that notwithstanding the use of experimental procedures designed to eliminate intentional bias, participants' perceptions were still systematically distorted in favour of their preferred teams. In addition, the findings suggested not only that the participants were unaware that they had made biased judgments, but also, that they rationalized their perceptions with reasons which endorsed and consolidated the partiality of their viewpoints. The results are discussed in terms of the potential for such personally construed processing to influence eyewitness accuracy and the implications for future research.